Caste differentiation pathways in the Neotropical termite Silvestritermes euamignathus (Isoptera: Termitidae) - Haifig, Ives [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Wiley, 2016)
Termites are hemimetabolous insects that commonly exhibit a bifurcation in post-embryonic development, with the presence of two lines: (i) the nymphal–imaginal line; and (ii) the apterous line. The former comprises the reproductive imagoes of the colonies and their preceding immature stages, whereas the latter is composed of workers, soldiers and their precursors. In this study, we analyzed the developmental pathways of caste differentiation in the Neotropical termite Silvestritermes euamignathus and compared it to the known sibling species, Silvestritermes holmgreni. Our results show that the apterous line is composed of male and female workers without sexual dimorphism and that soldiers are exclusively females. The imaginal line comprises five instars of nymphs, which may develop into either nymphoid neotenics or alates. Similarities found in our study between caste patterns of S. euamignathus and of S. holmgreni suggest a shared evolutionary history in these termite species. Some biological differences between the species are also discussed.
Keywords: castes; ergatoids; morphometry; nymphoids; phylogeny